Combination autologous stem cell transplantation with chimeric antigen receptor T-cell therapy for refractory/relapsed B-cell lymphoma: a single-arm clinical study - Li, Danyang; Liu, Rui; Fu, Zhonghua; Yang, Fan; Ma, Lixia; Guo, Yuelu; Cao, Miaomiao; Lei, Yang; Dou, Yimeng; Zhang, Xuenan; Gao, Yan; Wei, Bian; et al. (Frontiers in Immunology, 2025)
Autologous stem cell transplantation (ASCT) and chimeric antigen receptor T-cells (CAR-T) have been used as consolidation therapies for patients with refractory/relapsed B cell non-Hodgkin’s lymphoma (R/R B-NHL) in remission after second-line chemotherapy or salvage therapy. However, patients with different pathological subtypes and remission states may benefit differently from ASCT or CAR-T cell therapy. Furthermore, consolidation treatment involving ASCT or CAR-T cells still poses a significant risk of disease relapse. We conducted a retrospective, single-arm study of 47 patients with R/R B-NHL, and found that the combination of ASCT and CAR-T therapy improved the 3-year progression-free survival (PFS) and overall survival (OS) rates to 66.04% (95%CI: 48.311-78.928) and 72.442% (95%CI: 53.46-84.708) respectively. Furthermore, the combination therapy has no serious adverse events. Thus, ASCT combined with CAR-T cell therapy is effective against multiple subtypes of R/R B-NHL, and can effectively prolong the long-term survival of patients.